2020
DOI: 10.1111/jhn.12813
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sleep health on dietary intake: a systematic review and meta‐analysis of intervention studies

Abstract: Background: Poor dietary intake increases disease risk, and poor sleep influences diet. This systematic review and meta-analysis of intervention studies aimed to evaluate the effect of sleep health on dietary intake in adults. Methods: Five online databases were used to identify studies published between 1970 and 2019. Included studies were interventions that modified sleep and reported dietary outcomes. Results: Fifty four full texts were assessed and 24 publications were included. Following risk of bias appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 73 publications
1
31
0
1
Order By: Relevance
“…This may be because at baseline, both intervention groups reported sleep duration of ≈6.8 h per night, which was close to meeting the recommendation of 7–9 h per night for adults aged 18–64 years [ 68 ]. Relative to the much shorter sleep duration reported in meta-analyses that had an effect on dietary intake (≤5.5 h per night) [ 18 , 26 , 27 ], it may be that the participants’ sleep was not short enough and not improved enough during the intervention period to affect dietary behaviours (e.g., frequency of meals/snacks) and dietary intake. Furthermore, participants in the enhanced and traditional groups reported mean (SD) PSQI global scores of 7.3 (2.8) and 7.0 (3.1) at baseline, respectively.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This may be because at baseline, both intervention groups reported sleep duration of ≈6.8 h per night, which was close to meeting the recommendation of 7–9 h per night for adults aged 18–64 years [ 68 ]. Relative to the much shorter sleep duration reported in meta-analyses that had an effect on dietary intake (≤5.5 h per night) [ 18 , 26 , 27 ], it may be that the participants’ sleep was not short enough and not improved enough during the intervention period to affect dietary behaviours (e.g., frequency of meals/snacks) and dietary intake. Furthermore, participants in the enhanced and traditional groups reported mean (SD) PSQI global scores of 7.3 (2.8) and 7.0 (3.1) at baseline, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…The two intervention groups did not differ in sleep quality at 12 months, but the enhanced group was the only group to receive the sleep intervention, and it also had the largest improvement in sleep quality from baseline to 12 months. Given that sleep duration is related to sleep quality [ 67 ] and short sleep duration influences dietary intake [ 27 ], the improved sleep quality of the enhanced group may have contributed to the reduced intake of energy-dense nutrient-poor foods. Although to date, research has focused on how sleep duration and not sleep quality influences dietary intake, and further research is needed to clarify this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential mechanisms linking sleep with weight regulation include reduced activity levels among people with short duration or poor quality sleep [ 10 , 11 ]. Shorter sleep duration (<5.5 hrs/night) is also associated with increased energy intake, greater likelihood to select energy-dense foods, and poorer regulation of hunger [ 12 , 13 , 14 ]. Additionally, having poorer quality, shorter sleep duration (<7 hrs/night), or sleep-disordered breathing at the start of a traditional weight loss intervention is associated with lower weight loss in intervention studies [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that a lack of sleep increases the possibility of gaining weight and suffering from obesity due to different mechanisms that affect food intake and energy expenditure [ 6 , 7 ]. Additionally, good sleep quality is known to be essential for maintaining correct metabolic health and lower cardiovascular disease risk [ 8 ].…”
Section: Introductionmentioning
confidence: 99%